If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2(3 + -1d) = 4 4 + (3 * -2 + -1d * -2) = 4 4 + (-6 + 2d) = 4 Combine like terms: 4 + -6 = -2 -2 + 2d = 4 Solving -2 + 2d = 4 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2d = 4 + 2 Combine like terms: -2 + 2 = 0 0 + 2d = 4 + 2 2d = 4 + 2 Combine like terms: 4 + 2 = 6 2d = 6 Divide each side by '2'. d = 3 Simplifying d = 3
| 3p+q=-9 | | 38+5x=86+26 | | 3+42x=21x+30.0000000000004 | | Q-p=-1 | | x(2)+9x+20=0 | | 3.14*21cm^2*h= | | 5(2x+1)+2(x+4)=14 | | 6+3x=x-6 | | x(2)+x-6=0 | | -2/9m=12=-8 | | 3x^5-10x^3+16=0 | | x+(x*0.4)=199 | | (3.14)(21cm^2)(h)= | | 3(2-1)-2=4(-2)+5 | | x(2)+5x+6=0 | | y=3/7x-5 | | 4y=12x+18 | | 500=.075x-(750+.25x) | | 6(y+8)=8(b+5) | | x+(x*0.4)=278.60 | | (2-5)(22)(43)/2 | | 1/21(3x-2)^7 | | y/5-3.2=15.7 | | x+(x*.4)=676.60 | | 100=.04s | | (8y/y-2)-(16/y-2) | | 27x-18-6x-6=1+45x | | 200=0.04s | | 42+43=2 | | P=200+.14s | | x/5=f-32/9 | | 5=-13 |